1986
DOI: 10.1007/bf01907407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potassium conductance inhibitors on spontaneous diastolic depolarization and abnormal automaticity in human atrial fibers

Abstract: The capability of generating spontaneous diastolic depolarization and automaticity was investigated in vitro by means of standard microelectrode techniques in 50 human atrial preparations. Samples were classified within two groups: group 1 was composed of 12 well-polarized preparations exhibiting action potentials that were fast responses (mean maximum diastolic potential: -75.5 mV and Vmax greater than 100 V/s); group 2 was composed of 38 partially-depolarized samples (mean maximum diastolic potential: -50.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Thus late I Na is distinct from the Na ϩ window current, which is a steady-state, time-independent current that is present throughout the voltage range where the activation and inactivation relationships of I Na overlap (34). The potential for a role of late I Na in the genesis of DD lies in the fact that this inward current is present at voltages as negative as Ϫ70 mV in ventricular myocytes (33, 35) and Ϫ80 mV in Purkinje fibers (5); these membrane potentials are well within the reported voltage range for DD in atrial tissues (7,28,42). Because of its slow inactivation, late I Na may be activated during atrial DD, as suggested by the results of a previous study by .…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Thus late I Na is distinct from the Na ϩ window current, which is a steady-state, time-independent current that is present throughout the voltage range where the activation and inactivation relationships of I Na overlap (34). The potential for a role of late I Na in the genesis of DD lies in the fact that this inward current is present at voltages as negative as Ϫ70 mV in ventricular myocytes (33, 35) and Ϫ80 mV in Purkinje fibers (5); these membrane potentials are well within the reported voltage range for DD in atrial tissues (7,28,42). Because of its slow inactivation, late I Na may be activated during atrial DD, as suggested by the results of a previous study by .…”
mentioning
confidence: 90%
“…The results of experiments on cat atrial myocytes showed that both T-type Ca 2ϩ current [I Ca(T) ] and Na ϩ -Ca 2ϩ exchange current (I Na-Ca ) are involved in DD and abnormal automaticity (14), whereas the results of a study of human atrial fibers suggest a role for the pacemaker current I f in DD (7). On the other hand, a study of human atrial fibers (28) found that tetrodotoxin (TTX) markedly decreased the slope of DD, suggesting that a TTX-inhibited, slowly inactivating Na ϩ current (I Na ) may play a role in the development of atrial DD.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Several authors have related the great variability of results obtained in human atrial heart muscle (shape of the action potential, partial depolarization) to disease (Hordof et al, 1976;Ten Eick & Singer, 1979;Mary-Rabine et al, 1983;Escande et al, 1986;1987;Lee, 1986) or age (Escande et al, 1985) of the patients. In our hands, however, the quality of electrophysiological experiments seemed to be mainly determined by the procedure of isolation and further handling of the preparations.…”
Section: Preparationsmentioning
confidence: 99%
“…The precise ionic mechanism responsible for generation of the slow-type AAPs (CL > 2.0 s) in group 1 remains uncertain (EsCANDE et al, 1986). However, the slow activation of 'Ca' probably coupled with the deactivation of delayed rectifying K current (Ix, IMANISHI and SURAWICZ, 1976;KATZUNG and MORGENSTERN, 1977) seems to contribute to the development of the slow AAPs for the following reasons.…”
Section: Discussionmentioning
confidence: 99%